SEPER TOLEDOT ATAU BIBLOS GENESIOS: (Kajian Kitab Kejadian 5: 1-31 dan Matheus 1 : 1 - 17 tentang Geneologi Yesus Kristus) - Puji Swismanto (SAGACITY : Journal of Theology and Christian Education, 2022)
The purpose of this study is to find out about the genealogy of Jesus Christ which states that the incarnation did not occur spontaneously and has a long history. By examining the object of research in the book of Genesis 5:1-31 and Matthew 1:1-17 which is equipped with biblical supporting sources. The qualitative description method used in finding valid and accurate data aims to examine the object of research that is useful for obtaining data truths that can be used to draw a correct conclusion. Such as toledot and biblos genesios are words that can help in opening the data to understand that the incarnation did not occur spontaneously and went along with the plan of God's mission through the history of human life. The result of the research is that God's plan of salvation for a fallen world that went through the life of the first human Adam and was fulfilled in Jesus Christ did not occur spontaneously but through generations.